A Look at the Translation Process in Afghanistan's Higher Education Institutions in 2019 - Gol Mohammad Basil; Sayed Azimullah Esmati (پژوهش‌های ترجمه در زبان و ادبیات عربی, 2023)
In this research, an analytical-statistical method was used, and our main goal was to show the extent of the use of the translation process in the academic system of Afghanistan. The findings of this research indicate that the year (2019) had the highest number of subjects registered for translation compared to recent years. So, a difference of about 30% can be seen between the mentioned year and the previous year. Although the number of translated works has not been impressive so far, it is a good step towards strengthening the materials and resources for the researches of the country's academic system. The main question that was addressed was how to start the translation process in Afghanistan's higher education institutions in order to use the works and researches of other nations. So, it can be seen that the restoration process in the year (2019) was unprecedented in Afghanistan's higher education institutions compared to the 90s.Keywords: Translation, Goals, Motivation, Scientific Needs, Higher Education Institutions.   IntroductionTranslation is considered an excellent and vital approach in the process of teaching and transferring data and solving problems from one language and culture to another language and culture.Also, translation causes the sharing of theories, viewpoints, mindsets, and methods of scientific-literary studies among nations.Today's Afghanistan society, especially the academic and scientific generation needs access to academic texts more than ever. Undoubtedly, it is translation that can give a suitable answer to many of these needs and introduce relevant, enriched, and important texts for us.Translation has a history of thousands of years. Humans have used this approach since time immemorial to exchange their thoughts and opinions. Translation has always been used as a principle of interaction between living languages. But sometimes, due to its necessity, translation becomes an important matter, the denial of which causes unforeseeable losses in that society. Although many books from other languages have been translated into Farsi and other languages in different eras, in the mentioned periods, the passion for translation was so great that the activity of translation in those periods was called (translation movement). After the arrival of Islam, Muslim translators have played a very prominent role in translating from other languages into Arabic as the language of government, religion, and science. The process of translation has had many ups and downs in different periods of history. However, the chaotic situation and the ever-increasing disturbances have always prevented translation activity in Afghanistan. Despite the fact that some people called Afghan translators residing in other countries or within Afghanistan have tried to translate, there has been no effort to meet the needs of the society. If it is carefully considered, the practice of translation in other countries has specific goals and motivations that have made it flourish. In the absence of goals and motivation, one can never reach the destination, for example, Mohammad Ghazi says his motivation for translation is primarily (love for translation) and then (material needs). Languages are limited. In the same way, whoever has done the act of translation has also expressed his motivation. Although the historical course of translation in Afghanistan has been examined from different perspectives by translators abroad, we have explored and examined the translations of 2019 in state institutions of higher education led by the Ministry of Higher Education. The result obtained from it showed that in the early 90s due to the problems that affected the people of Afghanistan, the translation process was not taken care of much, but in the last half of this decade, we have witnessed the relative growth of this process; a number of books have been translated from international languages into the national languages of Pashto and Dari Farsi, for example, we can refer to books translated from Arabic, for example, Türkiye Meydan al-Sara' bein al-Sharq va al-Gharb was translated by a professor at Badakhshan University. From a literary point of view, this translation has some errors, because the translator is a history professor and does not know much about Persian grammar, which is why it has some literary errors. I have read this work once. Similarly, other works that have been translated into Pashto in other universities of the country are not free of literary errors. Because those who translate the books are not experts in the mentioned languages in terms of expertise. For example, the following books have been translated from Arabic to Pashto: the rules of fasting and philosophy in Dhu al-Qur'an and Sunnah, al-Zahreh fi fan al-Takhrij and Drasa al-Asatid, Taysir al-Qava'ed al-Narhulllambtadiin and the book of al-Qava’ed al-Ulama, Al-Adab and Fanoonah, Nizam al-Syasi fi al-Islam, which were translated by professors in Nangarhar and Kandahar universities, the only flawless translations that have been translated by language experts, among which the number of language experts is limited.Literature ReviewWe did not come across any articles about translation in Afghanistan's higher education institutions. Therefore, we decided to write an article about the activities carried out regarding the translation from other living languages to national languages.Significance of the StudyThis article has examined and researched the process of scientific-research translations in Afghanistan's higher education institutions in the year (2018). Moreover, it discussed some points about the translation services in higher education institutions which are done for scientific promotion of professors. For this reason, the present article is new in terms of content and is of great importance.Purpose of the StudyThe main purpose of translation research in higher education institutions is to reveal the services of Afghanistan's higher education academic staff members. Its partial goals are to estimate the amount of translation services provided according to the conditions, whether it is in accordance with the needs of the present age or not. Whether so many different works from living languages have been translated by the academic staff members of Afghan universities to meet the academic needs or not.Another secondary goal of this research has been to reveal this process with its importance and path along with objective evidence, so that every student and researcher can easily understand how many necessary works have been translated by the scientific staff members of higher education.Research Questions:What was the main purpose of starting translation in Afghanistan's academic institutions?How many of the desired works of Afghanistan's academic field have been provided through translation so far?To what extent can works translated from foreign languages into national languages of Afghanistan help in the scientific process of Afghanistan?MethodologyA statistical method has been used to investigate the problem. The statistical population of the mentioned research was the source of data from the Department of Research, Compilation, and Translation of the Ministry of Higher Education. Our way of working was that we first presented each university in separate tables, and then at the end of it, we analyzed the received data of works translated in all universities of Afghanistan in the year (2019).FindingsSo, we talked about the definition, literature review, purpose, significance, and questions of translation. The findings of this research show that the motivation for translation has increased among the academic staff members of some universities. This increase will bring hope for the translation process in the following years.Among the educational institutions, the professors of Kabul University have the highest motivation for translating the work from international languages to the national language, and in the second step is Nangarhar University, followed by academic members of Harat and Balkh universities. The experience of academic members and researchers shows that there have been significant considerations in the quantity and quality of the translated works. The most frequent and expressive translations in the year (2019) are the translations that have been translated using the semantic method (free meaning).The Importance of the Translation Process in Academic FieldsTranslation, as one of the simplest and most effective tools and means of communication between humans, has always received special and public attention throughout history. The requirements of the current era (technology) and the revolution of communication in the current century have made the lives of countries dependent on each other. The multi-dimensional reliance of the age of communication has forced contemporary people to be aware of each other's conditions and understand each other's needs.Therefore, the universities of Afghanistan, which are the cradle of science, and the members of its scientific staff are considered among the scientific and academic assets of the same society and expected to play their valuable part in the development of this process.ConlusionAfter many efforts for the present research and due to an agreement with the translation management department Research, Compilation, and Translation Department of the Ministry of Higher Education, we were able to obtain a relative database in which the scientific topics of the professors are recorded. The works of professors are registered in the database of scientific subjects based on the name of the translator, academic institution, and academic rank. But we proceeded by removing some things, and we only mentioned the name of the works, faculty, group, and year. Regarding the translated topics, it should be said that most of the translated topics are specialized and they have been translated according to the expertise of the group or field that was mentioned. In general, it can be said that the most translated works are from English and then from Arabic. Translators of works in Afghanistan's institutions of higher education have mostly used semantic methods (conceptual translation) and this is the usual and acceptable method of the Ministry of Higher Education of Afghanistan. The results obtained from the present research show that the most works for translation in the year (2019) were first registered at Kabul University, followed by Nangarhar University, Harat University, University of Medical Sciences, Sheikh Zayed University, Balkh University, and others, which is summarized in the diagram below.